The Implementation of Copilot-Based Artificial Intelligence (AI) Through Collage Techniques in Illustration Design - Dharma Prasetya Irawan; I Gede Wirya Mahendra Nandanawana Putra; Nauzidan Zakka Ramadhan; Kadek Darma Weda Wisesa (Primakara University, 2025)
The development of artificial intelligence (AI)-based illustrations, specifically using Copilot, in the creative industry has had a significant impact, opening new opportunities for designers to create visual works more efficiently and innovatively. The advantage of AI in analyzing and generating images makes the creative process faster and more varied. As this technology evolves, I am interested in developing a collaboration between AI-based collage techniques and illustration design. This research uses a descriptive analysis approach that combines observation, interviews/questionnaires, documentation, and literature study. Observations are made on the AI processes that I have created. Additionally, questionnaires are distributed to students from the Visual Communication Design department at Universitas Primakara to assess the importance and benefits of this technique in completing their assignments. The results of this research are expected to provide insights into whether this technique can help enhance creativity and efficiency in creating illustration designs, as well as contribute to the development of a more innovative creative industry.